The impact of accounting camp: a collaboration between Rajamangala University of Technology Srivijaya (RUTS) and Universiti Teknologi MARA (UiTM) - Kayurin, Lamun; Ahmad@ Said, Nadzir Awang; Saramas, Natcha; Osman, Amir Hakim; Abdullah, Azrul (Faculty of Accountancy, 2025)
The collaboration between Rajamangala University of Technology Srivijaya (RUTS) and Universiti Teknologi MARA (UiTM) Perlis Branch, began in 2023 through a simple academic group discussion at UiTM Perlis. From that modest beginning, the initiative grew into a meaningful annual Accounting Camp, conducted in 2023, 2024, and 2025. Each year, nearly 100 students and academic staff from both countries participated, forming strong cross-border bonds and sharing academic, cultural, and professional experiences. The main objective of the camp was to foster internationalization in accounting education - building academic knowledge while nurturing cultural understanding. This aligns with global trends that emphasize the importance of integrating international exposure into accounting curricula to enhance students' global preparedness (Wangwei & Judge, 2024). For students, the camp provided a platform to engage in cross-cultural academic dialogue, while faculty benefited from new insights into pedagogy and collaboration.